2016
DOI: 10.18176/jiaci.0042
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Modulates PTGDR Promoter Activity

Abstract: Background and Objective: Vitamin A has been linked to the development of allergic diseases although its role is not fully understood, Retinoic acid (RA), a metabolite of Vitamin A, has been previously associated with the prostaglandin pathway, and PTGDR, a receptor of PGD2, has been proposed as a candidate gene in allergy and asthma. Considering the role of PTGDR in allergy, the goal of this study was to analyze the effect of RA on the activation of the promoter region of the PTGDR gene. Methods: A549 lung ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…On the other hand, the experimental data showed that the CCCC construction, which combines both -549C and -197C mutated alleles, caused a significant increase in the promoter activity at 12 and 36 hours (basal conditions). This increased promoter activity reinforces previous results showing that the CCC (-549, -441, -197) combination was associated with higher luciferase expression at 12 and 48 hours [ 32 ]. In addition, in our expression experiment, both CCCC and CCCT haplotypes showed higher expression levels that the CTCT wild-type PTGDR haplotype (-613, -549, -441 and -197 positions).…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, the experimental data showed that the CCCC construction, which combines both -549C and -197C mutated alleles, caused a significant increase in the promoter activity at 12 and 36 hours (basal conditions). This increased promoter activity reinforces previous results showing that the CCC (-549, -441, -197) combination was associated with higher luciferase expression at 12 and 48 hours [ 32 ]. In addition, in our expression experiment, both CCCC and CCCT haplotypes showed higher expression levels that the CTCT wild-type PTGDR haplotype (-613, -549, -441 and -197 positions).…”
Section: Discussionsupporting
confidence: 90%
“…However, the role of RA in asthma and allergy is still controversial, [11,12,14]. We have previously reported that RA activated the PTGDR promoter, identifying RAREs in the promoter region and showing that transcription motifs were affected by genetic variants [17]. In the present study, we report for the first time the molecular mechanism of regulation of PTGDR expression by RA.…”
Section: Discussionmentioning
confidence: 54%
“…The wild-type PTGDR cDNA (NM_000953) was cloned in pCMV6-entry (OriGene, Rockville, MD, USA). The constitutive cytomegalovirus promoter of pCMV6- PTGDR was replaced by each one of the four promoter sequences of PTGDR haplotypes: CTCT, CCCT, TCCT and CCCC (-613C>T, -549T>C, -441C>T and -197T>C positions) [17,18]. Sequences were confirmed by sequencing and transformed into SoloPackGold Competent cells ( E .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations